Improving mobile networks based on social mobility modeling - Ribeiro, A.G.
Wireless networks growing popularity coupled with a wide availability of wireless-enabled personal devices is today the basis for user-centric Internet architectures to evolve. Central to this new paradigm of user-centricity is the fact that today the Internet end-user exhibits a highly nomadic behavior, where most of the portable devices are carried by humans. The thesis proposed relates to the recent trend of social mobility modeling as a way to improve mobile network operation. The work is focused on the analysis of social mobility models and how to propose new models having in mind an overall network optimization due to the possibility to predict adequately node movement on mobile networks.